Procedures for Carrying Out Flogging Punishment Against Gamblers Applied in Simeulue District, Aceh Province - Mus Mulyadi; Rahmayanti Rahmayanti; Muhammad Arif Sahlepi (Proceeding of the International Conference on Law and Human Rights, 2025)
Aceh is a province with special status in Indonesia that has special authority in the imple- mentation of Islamic law, as stipulated in Law No. 11 of 2006 concerning the Government of Aceh. One form of its implementation is Qanun Aceh No. 6 of 2014 on Jinayat Law, which regulates a number of offences, including maisir (gambling), with penalties in the form of flogging, fines, or im- prisonment. This study aims to examine the application of flogging for gambling offenders in Simeulue Regency, covering the legal basis, implementation procedures, and level of effectiveness. The research questions include: (1) how flogging is applied to gambling offenders; (2) what are the stages of imple- mentation; and (3) to what extent is it effective in reducing violations. The research uses a qualitative descriptive method with a socio-legal approach. Data was obtained through literature review, field observation, and interviews with Satpol PP and Wilayatul Hisbah officials, the Sharia Court, the pros- ecutor's office, and community leaders. The findings show that the application of flogging punishment has a strong constitutional basis and is in accordance with the principles of Sharia law. The implemen- tation is carried out openly in accordance with criminal procedure law and is supervised by medical personnel. Statistics from the last five years show a decrease in gambling cases from 11 cases in 2020 to 3 cases in mid-2024, reflecting a deterrent effect and an increase in compliance.